Influence of deproteinised foliage fluid liquid biofertilizer on nitrate reductase activity of Eleusine coracana plants - Jadhav, Rajesh K.; Chhaya, Gare (Current Botany, 2018)
Deproteinised leaf extracts previously found favourably enhancing plant and fungi growth. Present attempt has been made to observe its influence in enhancing the enzyme nitrate reductase. Crop of Eleusine coracana was cultivated and treated by deproteined whey from the leguminous weed Cassia tora and its influence examined on the activity of the enzyme nitrate reductase by spectrophotometric method. Cassia tora crop was fractionated for the purpose to isolate crude leaf protein by heating the juice to 90°C which gave deproteinised leaf juice (DPJ). The crop growth was also compared with other monocotyledonous wheat, Sorghum and bajra crops. There was enhancement of nitrate reductase in wheat crop by the application of non leguminous Basella forage DPJ. There was lesser activity of nitrate reductase in Eleusine crop by the influence of Cassia tora DPJ probably because of the deficiency of element molybdenum in the utilised red soil for the growth of crops or allelopathy. Length and number of leaves of Eleusine crop was measured.